Influence of Education Technology Innovation and Instructor Competency on Quality of Graduates with OHS (Occupational Health and Safety) - Pipa Biringkanae; Rifqi Raza Bunahri (Universitas Negeri Malang, 2025)
This study aims to analyze the effect of educational technology innovation and instructor competence on the quality of graduates, with the implementation of Occupational Health and Safety (OHS) as a mediating variable at Jayapura Aviation Polytechnic. This research falls under the category of quantitative research. The results show that educational technology innovation does not affect the quality of graduates, instructor competence has a positive effect on the quality of graduates, educational technology innovation does not affect occupational health and safety, instructor competence positively affects occupational health and safety (OHS), occupational health and safety positively affects the quality of graduates, OHS does not mediate the effect of educational technology innovation on the quality of graduates, and OHS mediates the effect of instructor competence on the quality of graduates. The conclusions from each discussion emphasize the need for an integrated approach in education management, where technology aspects, teaching competence, and occupational health and safety are interrelated and contribute to the quality of graduates. Research offers key insights for policymakers and stakeholders to develop effective and sustainable strategies for enhancing educational outcomes.